Effect of high trimline aligners on distalizing mandibular molars: a three-dimensional finite element study - Rugan Su; Song Li; Wei Wang (European Journal of Medical Research, 2024)
Abstract Objective The primary focus of this investigation was to evaluate the biomechanical effects of high trimline design aligners on the distalization of mandibular molars, employing three-dimensional finite element analysis (3D-FEA). The study concentrated on aspects such as tooth movement, stress distribution, and anchorage control. Methods Utilizing Cone-beam computed tomography (CBCT) data, a detailed 3D geometrical model was constructed for finite element analysis. This model was used to assess four variations of aligner trimlines, alongside the employment of Class III traction. Analyses were conducted to examine stress distributions and tooth displacements in these different scenarios. Results Aligners with a high trimline design were found to be more effective in facilitating the distal movement of mandibular molars than those with scalloped trimlines, providing improved management over tooth movement and stress distribution. In specific configurations where Class III traction was applied, a reduction in the deformation of anterior teeth was observed, which enhanced anchorage stability. Nevertheless, the anterior teeth in all configurations were subjected to compressive stresses that surpassed thresholds likely to induce external root resorption, underlining the importance of vigilant monitoring. Conclusions The research verified the biomechanical advantages of high trimline aligners in the distal movement of mandibular molars and underscored the critical role of aligner design and traction application in optimizing orthodontic treatment outcomes. Additionally, it raised concerns regarding the potential for root resorption due to significant stress in the periodontal ligament, necessitating thorough observation of patients, particularly those fitted with high trimline aligners. Despite these insights, the study’s findings are derived from the data of a single patient, suggesting a need for further investigations involving broader samples and extended clinical assessments.